IL-37 inhibits glycolysis of lung adenocarcinoma by inhibiting the expression of PFKFB3: IL-37 with Lung Adenocarcinoma - Liu, Chunwang; Peng, Rui; Nie, Zonglong; Zhao, Li; Zhu, Mingxue; Mu, Xiaofeng (Cellular and Molecular Biology, 2023)
Aerobic glycolysis is one of the hallmarks of cancer. The metabolic phenotype of tumor cells is characterized by preferential dependence on glycolysis under aerobic conditions. Recent researchers have provided a piece of information on the effectiveness of targeting glycolysis. Thus, targeted glucose metabolism therapy is still a research hotspot. Interleukin 37 (IL-37) plays an important role in tumor development. Previous studies have found that IL-37 can inhibit the progression of lung adenocarcinoma in a variety of ways. For example, IL-37 can inhibit the migration and invasion of lung adenocarcinoma by inhibiting the interleukin 6(IL-6)/ Signal transducing activator of transcription 3(STAT3) pathway. IL-37 inhibits tumor growth by regulating RNA methylation at the M6A site of lung adenocarcinoma. It has been found that overexpression of IL-37 in macrophages can reverse the Warburg effect. The mechanism of IL-37 on glucose metabolism of tumor cells has not been studied. In research, glucose uptake and lactic acid production were inhibited in A549 cells with recombinant human IL-37(rhIL-37). Also, rhIL-37 inhibited the expression level of PFKFB3 in A549 cells. To verify whether the two aspects of rhIL-37's effects on A549 cells are related, we applied PFK15, a specific inhibitor of PFKFB3, to prove that rhIL-37 inhibits the glucose uptake and lactate production of A549 cells by inhibiting the expression of PFKFB3, and further inhibits the progression of lung adenocarcinoma.